Penguatan Kapasitas Masyarakat melalui Program Sinergi Perguruan Tinggi: Sebuah Pendekatan Berkelanjutan di desa Cimarga Kabupaten Sumedang - Dedi Mulyadi (UNISBA Press, 2024)
Abstract. The joint implementation of One Village One Product (OVOP), stunting prevention, and digital literacy form the integral foundation for advancing the rural economy. With this holistic approach, rural communities can not only improve the production and marketing of local products, but also build healthy and competitive human capital, in line with the adaptation of the healthy and competitive, in line with adapting to the development of the digital era. This effort is not not only a long-term investment for rural progress, but also an important contribution to improving the welfare and to improving the overall welfare and sustainability of the national economy. Program KKN Thematic 3 with the theme